2014
DOI: 10.1007/s00330-014-3324-5
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of SE MRI and DWI of the spine in patients with monoclonal gammopathy of undetermined significance, smouldering myeloma and multiple myeloma

Abstract: • ADC values are higher in patients with MM compared to MGUS • DWI parameters change late in disease evolution • DWI is sensitive but not specific in diagnosing patients with MM • Qualitative DWI assessment is good in detecting myeloma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 27 publications
1
47
0
2
Order By: Relevance
“…In a previous study assessing mean ADC values before and after therapy in MM patients, ADC increased by 20% in therapy responders . Horger et al found an increase of ADC by 63.9% (range, 8.7–211.3%) 3 weeks after therapy onset in therapy responders, similar to the results of previous studies . Therefore, ADC mapping has shown to be a useful tool for the assessment of the disease course of MM.…”
Section: Applications Of Quantitative Bone Marrow Mri and Mrssupporting
confidence: 62%
See 2 more Smart Citations
“…In a previous study assessing mean ADC values before and after therapy in MM patients, ADC increased by 20% in therapy responders . Horger et al found an increase of ADC by 63.9% (range, 8.7–211.3%) 3 weeks after therapy onset in therapy responders, similar to the results of previous studies . Therefore, ADC mapping has shown to be a useful tool for the assessment of the disease course of MM.…”
Section: Applications Of Quantitative Bone Marrow Mri and Mrssupporting
confidence: 62%
“…For the detection of bone marrow infiltration in MM, DW images have been previously generated with EPI sequences (b values: eg, 0, 200, 400, 600, 1000 s/mm 2 ) . As mentioned previously, tissues with high cellularity contain a small interstitial space, which causes restricted water motion . Therefore, either focal lesions or diffuse tumor cell infiltration of bone marrow can be visualized as hyperintense DW signal.…”
Section: Applications Of Quantitative Bone Marrow Mri and Mrsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a higher ADC for T10 than for L3 was found by Dutoit et al . ; these results are summarized in Table . A slow decrease of the ADC with age was observed by Yeung et al .…”
Section: Adcs Of Normal‐appearing Vertebral Bone Marrowmentioning
confidence: 92%
“…It is more and more applied in oncologic imaging, apparent diffusion coefficient (ADC) being a parameter used to measure the magnitude of diffusion of water molecules within biologic tissues . Previous studies investigated the role of DWI in the differentiation between benign and malignant skeletal conditions, with promising results . However, studies performed in the spine had small sample size or lacked histology comparison .…”
mentioning
confidence: 99%